Aplikasi Model CA Schein pada PNS di Kota Pagar Alam - Meiliani .; Budiarto . (Universitas Kristen Maranatha, 2008)
Managing the careers of civil servants is important to the strategic use of government management. This study investigates CA’s profile of the Pagar Alam City‘s civil servants. Three hundreds seventy six usable questionnaires are obtained. The data strongly suggest that the dominant CA held by the respondents is multiple CAs. The Service CA is ranked in the second which has to be the first as its functions. Then, three new CAs with their new items emerge as CA dimensions, that is life satisfaction, idealism, and managerial skill making their career decisions. These results reveal that current situation forces civil servants to climb various of careers to fulfill their needs. So, the government needs to be careful to provide career paths in order to match the government needs and the civil servant needs. The theoretical and practical implications, the limitations, and the recommendation are discussed in this study.